2022
DOI: 10.1183/23120541.00207-2022
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with interleukin (IL)-5/IL-5 receptor antibodies in patients with severe eosinophilic asthma and COPD

Abstract: BackgroundAnti-eosinophilic therapy with interleukin-5/interleukin-5-receptor antibodies represents an established treatment for patients with severe eosinophilic asthma (SEA) but did not show clinical efficacy in patients with chronic obstructive pulmonary disease (COPD).ObjectiveTo evaluate treatment response to anti-eosinophilic antibody therapy in patients with Asthma and COPD.MethodsA retrospective comparison of pulmonary function testing, oral corticosteroid intake, quality of life and pulmonary symptom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In addition, although mepolizumab has exhibited favorable long-term safety in clinical studies (Gleich et al, 2021;Maspero et al, 2022), long-term safety data beyond 1 year in realworld settings are lacking. Moreover, mepolizumab has been approved recently for severe eosinophilic asthma in patients aged 6 years and older in many countries (Drick et al, 2022). However, there is limited data available to evaluate the safety of mepolizumab in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although mepolizumab has exhibited favorable long-term safety in clinical studies (Gleich et al, 2021;Maspero et al, 2022), long-term safety data beyond 1 year in realworld settings are lacking. Moreover, mepolizumab has been approved recently for severe eosinophilic asthma in patients aged 6 years and older in many countries (Drick et al, 2022). However, there is limited data available to evaluate the safety of mepolizumab in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…In COPD, the role of IL-5 and its potential targeting remains a conundrum. Indeed, some studies advocate for the use of anti-IL-5/IL-5R treatment [35][36][37] based on benefits on exacerbations while others call for more research to identify patients that would benefit from IL-5 targeting [38][39][40].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…However, a minor proportion of mepolizumab was used for COPD which was not included in the label. Despite the frequent coexistence and common pathophysiology of asthma and COPD ( Maspero et al, 2022 ), previous studies have reported inconsistent results regarding the efficacy of mepolizumab for COPD ( Drick et al, 2022 ; Ohnishi et al, 2022 ). Concerning the reporter countries, Canada and America accounted for most reports.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although mepolizumab has exhibited favorable long-term safety in clinical studies ( Gleich et al, 2021 ; Maspero et al, 2022 ), long-term safety data beyond 1 year in real-world settings are lacking. Moreover, mepolizumab has been approved recently for severe eosinophilic asthma in patients aged 6 years and older in many countries ( Drick et al, 2022 ). However, there is limited data available to evaluate the safety of mepolizumab in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%